In situ encapsulation of ultra small ceria nanoparticles stable at high temperatures in the channels of mesoporous silica - Ghosh, Sumona; Jijil, Chamundi P.; Devi, R. Nandini (Microporous and Mesoporous Materials, 2012)
Ultra small ceria nanoparticles of sizes <2 nm stable at 500 degrees C are encapsulated in the channels of mesoporous silica by employing a novel method of synthesis. The method involves modifying non-ionic polymer templates with ionic surfactants to enhance anchoring of metal ion precursors. In this way, further silica wall formation around the template ensures isolation of the nanoparticles exclusively within the channels after template removal by heat treatment. Further understanding of the interaction of the composite template system and cerium precursor is gained by cyclic voltammetric studies. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: ceria; Encapsulation; Mesoporous silica; Template synthesis